2012
DOI: 10.1159/000339509
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Linkage and Chromosome Maps of Red Clover (<b><i>Trifolium pratense</i></b> L.)

Abstract: Red clover (Trifolium pratense L.) is a forage legume and an allogamous diploid plant (2n = 14; 440 Mb). Here, we examine the 7 prometaphase chromosomes of red clover using fluorescence in situ hybridization (FISH) with ribosomal RNA sequences, pericentromeric and telomeric repeats, as well as bacterial artificial chromosome (BAC) clones. Position of hybridization signals and chromosome condensation patterns were quantified by the help of the chromosome image analysis system ver. 4.0 (CHIAS IV). Fourteen BAC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Variability within the 28 individual JEH plants was assessed using FISH on the level of different number and localization of both 5S and 45S rDNA. Hybridization of rDNA probes to maternal T. pratense shows 8 clusters of 5S rDNA repeats and 8 clusters of 45S rDNA repeats, which is in concordance with previous reports (Kataoka et al 2012). Hybridization to paternal T. medium shows 12 clusters of 5S rDNA loci and 8 clusters of 45S rDNA on separate chromosomes, and this has never been reported previously.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Variability within the 28 individual JEH plants was assessed using FISH on the level of different number and localization of both 5S and 45S rDNA. Hybridization of rDNA probes to maternal T. pratense shows 8 clusters of 5S rDNA repeats and 8 clusters of 45S rDNA repeats, which is in concordance with previous reports (Kataoka et al 2012). Hybridization to paternal T. medium shows 12 clusters of 5S rDNA loci and 8 clusters of 45S rDNA on separate chromosomes, and this has never been reported previously.…”
Section: Resultssupporting
confidence: 92%
“…Plant JEH 20/2 had a cluster of 5S rDNA surrounded by 45S rDNA clusters from both sides, and plants JEH 35/7 and 42/2 had a 45S rDNA cluster surrounded by 5S rDNA clusters from both sides (Figure 3). None of these formations has been observed to date in any other Trifolium species (Ansari et al 1999(Ansari et al , 2008Williams et al 2001;Kataoka et al 2012;Falistocco et al 2013).…”
Section: Resultsmentioning
confidence: 93%
“…The 5S rDNA loci were detected proximal to the NOR signals on the short arm of chromosome 1 and at another two loci on the short arm of chromosome 2. These results also demonstrated polymorphisms of rRNA genes and their locations among different varieties of red clover (Kataoka et al 2012). An Arabidopsis-type telomeric sequence (TTTAGGG)n was found to be present in red clover (Pedrosa et al 2002).…”
Section: Genome and Karyotypementioning
confidence: 65%
“…The lengths of the prometaphase chromosomes ranged from 5.1 to 7.4 μm, and uneven condensation patterns were observed that could be useful in chromosome identification. The genome structure of red clover using fluorescence in situ hybridization (FISH) was investigated by Sato et al (2005) and Kataoka et al (2012). Some chromosomes were distinguished using 26S and 5S rDNA probes.…”
Section: Genome and Karyotypementioning
confidence: 99%
“…The first consensus high-density linkage map contained 1,414 simple sequence repeats (SSRs), 181 amplified fragment length polymorphisms, and 228 restriction fragment length polymorphisms (Isobe et al, 2009). The structure of the red clover genome has been investigated using fluorescence in situ hybridization (Sato et al, 2005; Kataoka et al, 2012). The genome also has been compared with those of related species (white clover, M. truncatula and L. japonicus ) using DNA markers (Isobe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%